School creative climate: factors influence fostering creativity school - Vejian, Gajathiswari; Kamarudin, Nurzatulshima; Abdul Kadir, Suhaida (Universiti Putra Malaysia Press, 2016)
Through education, creativity can be nurtured and further enhanced. Creativity is seen as an influential and important factor in school to further develop the creativity especially in the school’s management as well as in the classroom teaching and learning process. As an important social factor, school creative climate can influence the teachers’ motivation, attitudes, behaviours and beliefs towards their daily work routine. Therefore, this conceptual paper is focusing on the discussion about the concept of school climate and school creative climate. In relation, the organizational climate theory relevant to creativity is also included in the discussion. Through the literature reviews, the applications of school creative climate in fostering creativity are also highlighted into discussion.